A Critical Review on the Book Advanced Accounting II of Payame Noor University - Ahmad Fathi Abdollahi; Mohammadreza Nikbakht; Arash Tahriri; Firooz Mahmoodi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The purpose of the study is to critically review the “Advanced Accounting II” book of undergraduate courses in accounting at Payame Noor University and analyze its problems. This research is a combination of the content analysis method to determine the typology of book problems and the descriptive method to examine the views of university professors. Jonassens prepared checklist was used to gather information and a researcher-constructed questionnaire was employed. Experts’ opinions were obtained for the justifiability of tools and for the reliability of the questionnaire Cronbach's alpha 0.98 was calculated. Results showed that from 51 problems of this textbook, 4 cases are algorithmic problems (8%), 34 cases are story problems (67%) and 13 cases are trouble-shooting problems (25%) and the most problems are algorithmic and story problems and the structure of them is well-structured. The content of the textbook does not fit with approved goals and dedicated time to presenting content is not enough and not updated over time, from professor's point of view its content is not up to date, as well as, not synchronous with the recent accounting standards and the content of the book is not suitable for students in terms of comprehensibility.